FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA PASIEN LANJUT USIA YANG BEROBAT DI POLIKLINIK PENYAKIT DALAM RUMAH SAKIT TK. II PUTRI HIJAU MEDAN - Resmi Pangaribuan (STIKes Mitra Husada Medan, 2020)
Hypertension is a disease with signs of systolic and diastolic blood pressure disorders that rise above normal blood pressure. Systolic blood pressure (numbers above) is the peak pressure that is reached when the heart contracts and pumps blood out through the arteries. Diastolic blood pressure is taken when the pressure falls to the point lowest when the heart relaxes and fills the blood again. Diastolic blood pressure is noted when the sound is not heard. The high level of hypertension in the Polyclinic at Putri Medan Hospital TK II in Medan is thought to be related to risk factors including age, sex, weight, genetic and lack of exercise.The purpose of this study was to determine the factors associated with the incidence of hypertension in the elderly in the Internal Medicine Polyclinic at Putri Hijau Hospital, Medan. This research is an analytic survey with cross sectional approach. The research sample was hypertension sufferers who went to the Internal Medicine Polyclinic at Putri Hijau Hospital, Medan. The study was taken by means of non random sampling using accidental sampling technique. Data was collected by questionnaire and physical examination in the form of measurements of body weight, height and blood pressure.Bivariate analysis results found that the p value <(0.05) is the age variable (0.010), and exercise (0.033). While the p value> (0.05) is gender (0.217), genetic (0.067), and weight (0.281). Based on the results of the study, it is recommended to sufferers and families to always maintain a healthy diet and live a healthy lifestyle, maintain body weight, the importance of controlling blood pressure. and to health workers, especially in the Internal Medicine Polyclinic at Putri Hijau Hospital in 2019, Medan always provides guidance and counseling in increasing information about hypertension in the elderly, its complications and treatment.